Literasi Keuangan Bank Sampah: Emas Digital Untuk Mengatasi Penurunan Nilai Poin DTBM dan Saldo Kas - Asep Risman; Budi Lestijawan Eka Saputra (Perbanas Institute, 2023)
The waste problem is still one of the problems faced by big cities, of course, it is also one of the problems in DKI Jakarta. Various efforts have been made by the DKI Jakarta government to reduce waste, including carrying out “Bank Sampah” (Waste Bank) activities in every sub-district. One of the Waste Bank in DKI Jakarta which is under the guidance of the West Jakarta Joglo sub-district is the Berdikari Waste Bank. The FEB Mercu Buana University Master of Management Study Program which already has a collaboration with the Universitas Pertahanan and also the Joglo Sub-District organizes community service activities at the Self-driving Waste Bank, one of the problems identified is the risk of decreasing DTBM point values and fund balances from time to time due to rising prices in general. Therefore, one of the topics in this community service is financial literacy for members of the Berdikari Waste Bank in the form of digital gold savings & investment to overcome the declining values of DTBM points and the fund’s balances of waste bank members as payment for waste deposits. Through this community service activity, it is hoped that it can help members of the Berdikari Waste Bank overcome the decline in DTBM point values and fund balances and improve the performance of the Waste Bank so that it will contribute more to overcoming the waste problem in DKI Jakarta.